2022
DOI: 10.1038/s41440-022-01020-0
|View full text |Cite
|
Sign up to set email alerts
|

Morning surge in sympathetic nervous activity in the indoor environment during the cold winter season

Abstract: We addressed to the sympathetic nervous activation of the same people in both their houses and a highly insulated and airtight model house (model house) during the cold winter season. Eight subjects (4 males and 4 females) stayed two nights at each house and were continuously monitored for sympathetic nerve system by calculating LF (low frequency)/HF (high frequency) in the analysis of heart rate variability using a wearable electrocardiography equipment. The room temperatures were kept constant at 20 °C or mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…The impact of ambient temperature upon autonomic activity and BP control in humans was recently highlighted by Nakagami et al, 27 who demonstrated that ambient home temperature during cold winter months modulates the morning surge in sympathetic nervous activity and BP in humans. This observation is important because the morning surge in BP is a known, strong predictor of cardiovascular events.…”
Section: Discussionmentioning
confidence: 97%
“…The impact of ambient temperature upon autonomic activity and BP control in humans was recently highlighted by Nakagami et al, 27 who demonstrated that ambient home temperature during cold winter months modulates the morning surge in sympathetic nervous activity and BP in humans. This observation is important because the morning surge in BP is a known, strong predictor of cardiovascular events.…”
Section: Discussionmentioning
confidence: 97%